Review on Chamber-Specific Differences in Right and Left Heart Reactive Oxygen Species Handling - Schlüter, Klaus-Dieter; Kutsche, Hanna Sarah; Hirschhäuser, Christine; Schreckenberg, Rolf; Schulz, Rainer (Frontiers in Physiology, 2018)
Reactive oxygen species (ROS) exert signaling character (redox signaling) or damage cardiac tissue (oxidative stress) depending on their concentration and/or reactivity. The ROS concentration is determined by the interplay between its production (mitochondrial, cytosolic and sarcolemmal enzymes) and ROS defense enzymes (mitochondria, cytosol). Recent studies suggest that ROS regulation is different in left and right ventricles especially under pathophysiological conditions. Specifically, mitochondrial ROS defense seems to be lower in right ventricular tissue compared to left ventricular tissue. In this review we summarize the current evidence for heart chamber specific differences in ROS regulation that may play a major role in an observed inability of the right ventricle to compensate for cardiac stress such as pulmonary hypertension. Based on the current knowledge regimes to increase ROS defense in right ventricular tissue should be in the focus for the development of future therapies concerning right heart failure.